绿原酸对高脂饲料诱导的肥胖大鼠糖耐量及其曲线特征的影响 (Beijing Da Xue Xue Bao Yi Xue Ban, 2020)
OBJECTIVE: To observe the effect of chlorogenic acid (chlorogenic acid,CGA) on the glucose tolerance and its curve characteristics in high fat diet-induced obesity (diet-induced-obesity,DIO) rats, so as to provide scientific grounds for the development and utilization of CGA in early prevention and reversal of prediabetes. METHODS: Eight of forty-six male Sprague-Dawley rats were randomly selected as the normal diet group (CON group), and the rest were fed with high-fat diet. After 4 weeks, 24 high-fat-induced obese rats were screened according to the criteria and then randomly divided into high fat diet group (HFD group), 50% CGA group and 98% CGA group. The CGA groups received intragastric administrations of 50% CGA and 98% CGA orally via a gavage needle once a day for 8 weeks, respectively, while the CON and HFD groups received a carrier solution (phosphate buffer saline, PBS). Their body weights were measured weekly and oral glucose tolerance test (OGTT) was performed every 4 weeks. Fasting insulin and insulin release were measured at the end of the study. Meanwhile, HOMA-IR and visceral fat percentage were calculated. Histopathological examination by hematoxylin and eosin staining method were evaluated in the pancreatic tissues. RESULTS: Before the intervention of chlorogenic acid, blood glucose levels 120 min after glucose loading (P<0.05) and AUC-G (P<0.05) were increased in the HFD group when compared with the CON group, and the time to glucose peak was delayed after 4 weeks of chlorogenic acid intervention (P<0.05). After 8 weeks of intervention, the HOMA-IR index, the insulin levels at 0 min, 30 min, 60 min, and 120 min after glucose loading and AUC-I increased (P<0.05), and the histopathological examination showed obvious hyperplasia of pancreatic islets (P<0.05). Compared with the HFD group, there was no significant change in glucose tolerance and glucose peak time in 50%CGA and 98%CGA groups at the end of 4 weeks of intervention. How-ever, after 8 weeks of intervention, OGTT-60min,OGTT-120min blood glucose (P<0.05) were lower, HOMA-IR index and OGTT-0min, OGTT-120min serum insulin level decreased (P<0.05), the time to glucose peak shifted to an earlier timepoint (P<0.05), abnormal islet hyperplasia attenuated (P<0.05) in 50% CGA and 98% CGA groups. Also, the OGTT-30min serum insulin level was decreased (P<0.05) in 50% CGA group. CONCLUSION: Delay in time to glucose peak during the OGTT was one of the manifestations of impaired glucose tolerance in DIO rats, and 50% and 98% CGA could improve the glucose tolerance and delay in glucose peak time.